Unsupervised trajectories of respiratory/allergic symptoms throughout childhood in the PARIS cohort. Issue 3 (7th March 2019) - Bougas, Nicolas; Just, Jocelyne; Beydon, Nicole; De Blic, Jacques; Gabet, Stephan; Lezmi, Guillaume; Amat, Flore; Rancière, Fanny; Momas, Isabelle
Abstract: Background: Natural course and co‐occurrence of asthma, eczema, and allergic rhinitis through childhood are still not fully documented. We aim to identify and characterize profiles based on the time course, severity, and apparent triggers of respiratory/allergy symptoms in school‐aged children. Methods: Data on occurrence, severity, and triggers of asthma, rhinitis, and dermatitis symptoms were collected annually during the follow‐up of the PARIS birth cohort. Children with similar symptom trajectories until 8‐9 years were grouped into profiles using multidimensional (all symptoms considered simultaneously) cluster analysis. Associations between profiles and different health outcomes were analyzed using logistic or linear regression models. Results: Six distinct symptomatic profiles were identified. A profile was defined by persistent dermatitis symptoms, associated with sensitization to food and aeroallergens. Two profiles were characterized by wheezing: one with early transient wheezing and the other with persistent wheezing related to doctor‐diagnosed asthma, airway obstruction, and perennial aeroallergen sensitization. Three profiles were characterized by rhinitis symptoms: one non‐allergic and two allergic, either with persistent rhinitis symptoms related to allergic multimorbidity and sensitization to perennial aeroallergens, or with late‐onset symptoms, related to both pollen and perennial aeroallergens sensitization as well as low lung function. Conclusion: This study brings further insights into the developmental profiles of respiratory/allergic outcomes from birth to school age. The identified profiles clearly differed regarding objective features such as diagnosed morbidity, sensitization, or lung function measurements, thus highlighting their biologic and clinical relevance. Allergic rhinitis profiles deserve particular attention, since they were likely to be involved in multimorbidity patterns.